2017
DOI: 10.1039/c6nr08507e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing electrochemical detection of dopamine via dumbbell-like FePt–Fe3O4nanoparticles

Abstract: We synthesize dumbbell-like FePt-FeO nanoparticles (NPs) and study their electrocatalytic oxidation and sensing of dopamine (DA). The FePt and FeO NPs are strongly coupled in the dumbbell structure and as a result, the dumbbell FePt-FeO NPs show the best activity for DA oxidation with the DA detection limit reaching 1 nM. They are used successfully to monitor the DA concentration increase induced by K-stimulation of PC12 cells. Our data show that an electrode modified with dumbbell-like FePt-FeO NPs can serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Metal oxide nanoparticles and nanostructures can also be used for electrochemical sensing of dopamine owing to their high surface area and good biocompatibility [70]. Thus, iron oxide and platinum were synthesized to prepare dumbbell-like FePt-Fe 3 O 4 nanoparticles, which electrocatalyzed the oxidation and increased the sensing of dopamine, leading to a linear range of 0.1-90 µM and a detection limit of 1 nM [71] (Table 2). They were also used successfully to monitor the dopamine released from PC12 cells stimulated with K + (extracellular K + is very frequently used to induce a release of positively charged dopamine molecules by living cells).…”
Section: General Overview Of Modification Materials Formentioning
confidence: 99%
“…Metal oxide nanoparticles and nanostructures can also be used for electrochemical sensing of dopamine owing to their high surface area and good biocompatibility [70]. Thus, iron oxide and platinum were synthesized to prepare dumbbell-like FePt-Fe 3 O 4 nanoparticles, which electrocatalyzed the oxidation and increased the sensing of dopamine, leading to a linear range of 0.1-90 µM and a detection limit of 1 nM [71] (Table 2). They were also used successfully to monitor the dopamine released from PC12 cells stimulated with K + (extracellular K + is very frequently used to induce a release of positively charged dopamine molecules by living cells).…”
Section: General Overview Of Modification Materials Formentioning
confidence: 99%
“…As a promising strategy for boosting performance of catalysts, the interfacial engineering, representing the interaction between multicomponent, brings a new opportunity for the enhanced catalytic activity, stability, and selectivity. [ 98 ] Generally, the interface in catalysts refers to the boundary between different regions where electrocatalysis mainly occurs. The interfacial active sites can usually balance the adsorption/desorption for intermediates and tune the transportation of electron and mass, thus achieving the enhanced catalytic performance.…”
Section: Advanced Regulation Of Pd‐based Nanomaterials For the Enhanced Electrocatalysismentioning
confidence: 99%
“…In addition to oxides, many other compounds, including metal sulfides, phosphides, hydroxides, and so on, have also been found to couple with Pd‐based materials for improving electrocatalytic performance. [ 105 ] More recently, Bao et al demonstrated that the formed Pd/FeP interfacial sites are more active than exclusive Pd sites [105d] . By annealing inactivated Pd/FeP composites, Pd/FeP hereostructures with abundant interfacial sites were achieved, much more efficient for FAOR than pristine Pd/FeP.…”
Section: Advanced Regulation Of Pd‐based Nanomaterials For the Enhanced Electrocatalysismentioning
confidence: 99%
“…In 2017, Yang. W. et al synthesised iron oxides and platinum to create a FePt-Fe 3 O 4 dumbbell-like nanostructure and measured dopamine [60]. The electrode was fabricated by repeated heating and cooling, and the disposal-precipitation processes were repeated.…”
Section: Morphologically Transformed Metal Oxide-based Dopamine (Da) mentioning
confidence: 99%